GEREJA YANG RAMAH ANAK: PELAYANAN HOSPITALITAS PADA PENYANDANG DISABILITAS - simanjuntak, wilda (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2023)
A “child friendly church” is a phrase that is often heard at this time. It is important to struggle and explore the meaning contained in it. Emphasizing the hope that churches convey a prophetic voice and become a blessing to the world. The church is a meeting room for the sacredness of the congregation with God. Those who are called out of darkness into the light of God. It is Christ who is the head of the church - its Savior of the world. The Church is open to all. A church that welcomes all members of the congregation including children, youth, adults, the elderly, and people with disabilities as citizens of God's kingdom. There is no reason to exclude or possibly exclude them from the community of believers. The point of concern that needs to be emphasized is how to educate parents, children and teachers to be an open and welcoming community offering hospitality and providing a comfortable space for persons with disabilities in which to be part of the community of faith Keywords: ‘Child friendly church’; Hospitality; Disability